Contribution of Domestic Direct Investment and Direct Foreign Investment to Economic Growth in Indonesia Era Joko Widodo - Darwanti, Dhenok; Darman,; Yolanda, (International Journal of Business, Economics and Management, 2020)
This study aims to analyze the contribution of Domestic Investment (DDI) and Foreign Investment (DFI) to economic growth in Indonesia under President Jokowi. The data used are the 2014-2019 quarterly time series from the Word Bank, BPS and BPKM. This research uses descriptive quantitative method, with multiple regression analysis with SPSS. Hypothesis testing uses the t test (partial test) and F test (simultaneous test) with a significance of α = 0.05. The results of hypothesis testing show that partially FDI has a negative effect on economic growth in Indonesia, while DDI has no significant effect on economic growth. However, simultaneously DDI and FDI have no significant effect on economic growth. At the end of the study, it is suggested that the role of the government as a regulator is needed to increase DDI and FDI so as to increase economic growth. Furthermore, Indonesia needs to improve the quality of innovative human resources as an attraction for investors to invest in Indonesia, such as Malaysia, Thailand and Vietnam.